The Prevalence of Post-Abortion Grief and the Contributing Factors - Sompong Kanchanapusit; Wiboolphan Thitadilok; Supachoke Singhakan (The Royal Thai College of Obstetricians and Gynaecologists, 2009)
Objective: To study the prevalence of post-abortion maternal grief and the contributing factors that might relate to its occurrence. Design: Cross-sectional, descriptive study. Subject: The 289 post-abortion women of less than 28 weeks' gestation without the history or during psychiatric treatment admitted at the post-abortion ward, Department of Obstetrics and Gynecology, Siriraj Hospital, between August 20, 2008 and March 19, 2009 were nrolled. Materials and Methods: The studied groups were requested to complete the questionnaires elating the demographic characteristics, the history of the previous and present pregnancy and the Perinatal Grief Scale (PGS) within the first 24-48 hours after abortion. The collected data was analyzed to determine the prevalence and the contributing factors of post-abortion maternal grief. Results: The prevalence of severe (despair), moderate (difficulty coping) and mild (active/ normal) grief intensity were 4.8% (95%CI 2.9-8.0), 67.8% (95%CI 62.2-72.9) and 27.4% (95%CI 22.5-32.7) respectively. The four contributing factors of post-abortion grief were the patient age (<20 yrs) (OR 3.1, 95% CI 1.1-8.5), husband age (20-35 yrs) (OR 1.7, 95% CI 1.0-3.0), level of education (secondary school) (OR 1.9, 95% CI 1.0-3.5) and family income (<10,000 Baht/month) (OR 3.3, 95% CI 1.5-7.3). After multiple logistic regression test was done only one factor-'income <10,000 Baht/month'- remained significant (p<0.05). Conclusion: The abnormal grief ('Difficulty coping' and 'Despair') after abortion occurs very often with the prevalence of 72.6% (95%CI 67.3-77.5). The screening of patients at risk such as those with age < 20 years, less than 'secondary level' education, and especially those with family income below 10,000 Baht/month is necessary for the prevention of any psychological sequel.